Exposure-response relationships in asthma caused by tetrachlorophthalic anhydride. - Venables, K; Newman Taylor, A (1990)
Four patients with asthma caused by occupational exposure to tetrachlorophthalic anhydride (TCPA) had dust-challenge tests that used eight different levels of TCPA exposure. Measurements of TCPA in the test-cubicle air ranged from 1.3 to 961.1 micrograms/m3. The higher exposures provoked definite late or dual asthmatic responses. Smaller, but statistically significant, responses were observed at low exposures. The late asthmatic-response area had a linear relation to the logarithm of TCPA exposure, but the immediate asthmatic response was less closely related to exposure.